2011
DOI: 10.1177/1012690211414343
|View full text |Cite
|
Sign up to set email alerts
|

The rise of the underdog? The relative age effect reversal among Canadian-born NHL hockey players: A reply to Nolan and Howell

Abstract: The relative age effect associated with cut-off dates for hockey eligibility has been an ongoing debate in certain academic circles and in the popular media. The effect is primarily found in Canadian Major Junior Hockey, where a disproportionate share of birthdays fall in the first three months of the year. But when the National Hockey League rosters of Canadian-born players are examined, the pattern is less pronounced. Using publically available data of hockey players from 2000-2009, we find that the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
186
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(205 citation statements)
references
References 6 publications
19
186
0
Order By: Relevance
“…December) in their next oldest age group. The observation is seemingly consistent with the 'underdog hypothesis' which suggests that younger and/or later maturing athletes need to be physically, technically, and psychologically 'ahead of the curve' in order to remain competitive within such programs (36). The results also suggest that older and/or early maturing males get by on their physical prowess rather than their technical or tactical abilities.…”
Section: Youth Soccer Players Enrolled In the Talent Development Progsupporting
confidence: 78%
See 1 more Smart Citation
“…December) in their next oldest age group. The observation is seemingly consistent with the 'underdog hypothesis' which suggests that younger and/or later maturing athletes need to be physically, technically, and psychologically 'ahead of the curve' in order to remain competitive within such programs (36). The results also suggest that older and/or early maturing males get by on their physical prowess rather than their technical or tactical abilities.…”
Section: Youth Soccer Players Enrolled In the Talent Development Progsupporting
confidence: 78%
“…It can be argued that the greater challenge associated with being the youngest and/or least mature serves as a stimulus towards superior long term development. This argument was first advanced by Krogman (47) and is embedded in the 'underdog hypothesis' of Gibbs and colleagues (36), which states that those youth who experience the greatest physical challenges are more likely to develop the technical and psychological attributes necessary for success at the adult professional level. The argument only holds, however, if the challenge is manageable and if the athlete is recruited into and/or retained by the system.…”
Section: Bio-banding and Competitionmentioning
confidence: 99%
“…This relates to a combination of factors related to catch-up in growth and maturation, motivation and systematic efforts to nurture, perhaps to protect, skilled late maturing athletes during adolescence. It has been suggested that late maturing boys within a CA group may have more athletic potential as young adults due to challenges experienced during adolescence 91. To remain competitive with peers, the late maturing boy compensates for physical disadvantages by developing superior technical and strategic skills and/or a more adaptive, resilient psychological profile.…”
Section: Implications For the Development Of Youth Athletesmentioning
confidence: 99%
“…When hockey success is defined as the most elite levels of play, the relative age effect reverses [i.e., later born players outperform their early born counterparts]." Gibbs et al (2012) only compare means and do not control for individual confounders such as country and team effects; as such, empirically we feel the jury is still out.…”
mentioning
confidence: 99%